Pendekatan Hermeneutika Kontekstual dalam Menafsirkan Narasi Penciptaan: Studi Komparatif Metodologis antara Islam dan Kristen - Siti Azurah; Nikson Siallagan (Kamali: Jurnal Ilmu Agama, 2025)
A contextual hermeneutic approach is crucial in understanding the narrative of human creation so that interpretations of religious texts do not fall into reductive and ahistorical literal readings. This article aims to analyze and compare the methodology of contextual hermeneutics in the Islamic and Christian traditions to discover epistemological patterns and their theological implications for the interpretation of the creation story. This research uses a qualitative approach with a comparative-hermeneutic analysis method, which relies on primary sources such as the Quran, the Bible, and works of classical and modern hermeneutic interpretation and commentaries, accompanied by a review of contemporary academic literature. The results show that contextual hermeneutics in Islam, as developed by thinkers such as Fazlur Rahman and Nasr Hamid Abu Zayd, emphasizes the close relationship between the text and its socio-moral context. The text is understood as a living discourse in history, demanding the reader’s intellectual engagement to uncover ethical messages and universal values ​​that are in line with the dynamics of modern society. In contrast, in the Christian tradition, contextual hermeneutics, represented by Paul Ricoeur and Hans-Georg Gadamer, places greater emphasis on the symbolic, existential, and dialogical aspects of the creation narrative, where meaning is understood as the result of the encounter between the text’s horizon and the reader’s horizon in the experience of faith. A comparison of the two reveals a common ground in contextual awareness, an appreciation for the dynamics of meaning, and the active role of the interpreting subject. The conclusion of this study confirms that contextual hermeneutics, both in Islam and Christianity, can serve as a foundation for the development of interfaith interpretive discourse that is more dialogical, inclusive, and responsive to the challenges of contemporary humanity.